2021
DOI: 10.1111/myc.13387
|View full text |Cite
|
Sign up to set email alerts
|

Global epidemiological burden of fungal infections in cirrhosis patients: A systematic review with meta‐analysis

Abstract: Background and Aims: Fungal infections (FIs) have serious implications, yet understated in cirrhosis. Therefore, we reviewed the epidemiology and trends of FIs among cirrhotics.Methods: Four electronic databases were searched for full-text articles describing prevalence of FIs in cirrhosis. Studies from post-transplant, malignancy and classicalimmuno-deficiency patients were excluded. A random-effects meta-analysis was done to pool estimates of FIs (overall, and by type and infection-site), and their variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 71 publications
1
26
0
Order By: Relevance
“…We showed that ACLF and ICU‐admitted patients are the two high‐risk categories among cirrhosis that warrant closer attention. This was in line with our previous reports on the highest‐burden of FIs, 5 the highest risk of death due to IC, 9 and IA, 8 specifically in these two categories of patients. However, studies mediating the mechanisms for such a risk are currently lacking and need further exploration.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We showed that ACLF and ICU‐admitted patients are the two high‐risk categories among cirrhosis that warrant closer attention. This was in line with our previous reports on the highest‐burden of FIs, 5 the highest risk of death due to IC, 9 and IA, 8 specifically in these two categories of patients. However, studies mediating the mechanisms for such a risk are currently lacking and need further exploration.…”
Section: Discussionsupporting
confidence: 93%
“…We showed that hospitalised cirrhosis patients, especially those in ICU, are at risk of developing and eventually dying due to FIs. 5,8,9 Such patients are often in ACLF and have alcoholic hepatitis or gastrointestinal bleeds, which severely compromise the gut-liver axis allowing endogenous translocation of altered mycobiome leading to dysregulated immune response and poor outcomes. 62 Our findings indicate that the mortality is higher in patients with pulmonary FIs followed by peritoneal FIs and fungemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations